Comparison of Zoonotic Bacterial Agents in Fleas Collected from Small Mammals or Host-Seeking Fleas from a Ugandan Region Where Plague Is Endemic - Bai, Ying; Osikowicz, Lynn M.; Kosoy, Michael Y.; Eisen, Rebecca J.; Atiku, Linda A.; Mpanga, Joseph T.; Boegler, Karen A.; Enscore, Russell E.; Gagea, Kenneth L. (Msphere, 2017)
Fleas (n 407) were collected from small mammals trapped inside huts and surroundings of homesteads in five villages within the Arua and Zombo districts of Uganda. The most common flea species were Dinopsyllus lypusus (26%) and Xenopsylla cheopis (50%). Off-host fleas (n 225) were collected inside huts by using Kilonzo flea traps. The majority of the off-host fleas were Ctenocephalides felis (80%). All fleas were examined for the presence of Bartonella spp., Rickettsia spp., and Yersinia spp. Bartonella DNA was detected in 91 fleas, with an overall prevalence of 14%. Bartonella prevalence was significantly higher in rodent or shrew fleas than in off-host fleas (22% versus 1%). The majority of Bartonella-positive fleas were of the species D. lypusus (61%), X. cheopis (20%), and Ctenophthalmus calceatus (14%). Sequencing analysis identified 12 Bartonella genetic variants, 9 of which belonged to the zoonotic pathogen B. elizabethae species complex. Rickettsia DNA was detected in 143 fleas, giving an overall prevalence of 23%, with a significantly higher prevalence in off-host fleas than in rodent or shrew fleas (56% versus 4%).
Keywords: Bartonella; Rickettsia; Uganda; Yersinia; Fleas; Off-host; Rodents